Clinical presentation and management of parapharyngeal space tumours - Anwar, Mostafa Mahfuzul (Bangladesh Journal of Otorhinolaryngology, 2011)
Methods: Tumors originating in the parapharyngeal space are uncommon. During the period of January 1999 to December 2008. Among them 34 patients underwent surgery for parapharyngeal space tumors at the Department of Otolaryngology and Head Neck Surgery, Chittagong Medical College Hospital. Results: Ninety one percent of the parapharyngeal space neoplasms were benign; 9% were malignant. Majority of the benign tumors were salivary gland origin followed by neurogenic tumors. The use of FNAC, computed tomography scan and ultrasound imaging are very useful to assess the location, size, vascularity, tissue origin and relation of parapharyngeal space tumors to surrounding anatomical structures. Conclusion: This information was essential in planning surgical approaches and predicting the prognosis. Details of the management, morbidity, and outcome of these patients were presented. Key words: Tumor; Parapharyngeal space. DOI: 10.3329/bjo.v17i1.7626 Bangladesh J Otorhinolaryngol 2011; 17(1): 36-41